Positioning of light shelves to enhance daylight illuminance in office rooms - Badri Narayan Mohapatra; M. Ravi Kumar; Sushanta Kumar Mandal (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper aims to improve daylighting by using light shelves. Horizontal light shelf is found to increase the illuminance in the interior of office rooms. By tilting external light shelf more illuminance can be achieved. For uniformity of illuminance tiltable light shelf is the best choice instead of horizontal light shelf. The performance of light shelves was examined through simulations on DIALux and compared with experimental values obtained from a prototype. Substantial improvement in illuminance is obtained in the experimental studies with tilted light shelves on the prototype.